Mining smartness from nature : selected, peer reviewed papers from the symposium H Mining smartness from nature of CIMTEC 2012-4th international conference Smart materials, structures and systems, held in Montecatini Terme, Italy, June 10-14, 2012 - Vincenzini, P., 1939- (Advances in science and technology (Faenza, Italy), 2013)
The 12 peer-reviewed papers collected here together offer a plenitude of up-to-date information on ""Mining Smartness from Nature"". The papers are conveniently arranged into: Chapter 1: Biomimetic Materials, Chapter 2: Biomimetic Sensors, Actuators and Systems, Chapter 3: Biomimetic Flow Control. Review from Book News Inc.: Vincenzini (World Academy of Ceramics, Italy) et al. bring together 12 papers presented by researchers working in biomedical materials, engineering, biology, zoology, and other areas in Europe, Brazil, and Asia at Symposium H, ""Mining Smartness from Nature, "" of CIMTEC 20